2006
DOI: 10.1016/j.bbadis.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte and plasma protein modification in alcoholism: A possible role of acetaldehyde

Abstract: Analysis of the oxidative modification of plasma and erythrocyte ghost proteins of chronic alcoholic subjects and healthy non-alcoholics has been performed. It was found that increased levels of protein carbonyls in both plasma and erythrocyte ghosts from alcoholic subjects occurred in comparison to the levels found in preparations from non-alcoholics. Plasma proteins from alcoholic subjects did not show evidence of cross-linking, although plasma protein concentration and composition were changed. In alcoholic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…Our data thus confirm the results of an unchanged whole blood viscosity in vitro [18] and in vivo [30] with the same amount of 0.5 g alcohol (wodka)/kg BW or even a three times higher amount of 1.5 g alcohol/kg BW [22]. Besides the osmotic shrinkage, erythrocytes may undergo some degree of echinocytic shape transformation when high ethanol concentrations are used [26] and membrane proteins may become oxidized and crosslinked by acetaldehyde [45], a product of ethanol metabolism. We have not studied erythrocyte morphology in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Our data thus confirm the results of an unchanged whole blood viscosity in vitro [18] and in vivo [30] with the same amount of 0.5 g alcohol (wodka)/kg BW or even a three times higher amount of 1.5 g alcohol/kg BW [22]. Besides the osmotic shrinkage, erythrocytes may undergo some degree of echinocytic shape transformation when high ethanol concentrations are used [26] and membrane proteins may become oxidized and crosslinked by acetaldehyde [45], a product of ethanol metabolism. We have not studied erythrocyte morphology in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Elevated plasma albumin levels have also been demonstrated to be present in alcoholics, and the albumin levels were found to correlate with the amount of protein carbonyls, suggesting that covalent modifications of proteins by acetaldehyde could also be associated with albumin protein expression in heavy drinkers (32). In vitro studies on this topic have shown elevated hepatic protein synthesis rates as a result of chronic ethanol administration in cell cultures (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Normal RBC deformability is essential for proper tissue perfusion and oxygenation, as well as the normal survival of RBC in the circulation. Therefore, maintaining normal RBC mechanical properties should be an important objective in therapeutic approach to some hematological and other disorders [8,16,17].…”
Section: Introductionmentioning
confidence: 99%